Innovative firms or innovative owners? Determinants of innovation in micro, small, and medium enterprises - Suresh de Mel; David McKenzie; Christopher Woodruff (Institute for the Study of Labor (IZA), 2009)
Innovation is key to technology adoption and creation, and to explaining the vast differences in productivity across and within countries. Despite the central role of the entrepreneur in the innovation process, data limitations have restricted standard analysis of the determinants of innovation to consideration of the role of firm characteristics. We develop a model of innovation which incorporates the role of both owner and firm characteristics, and use this to determine how product, process, marketing and organizational innovations should vary with firm size and competition. We then use a new large representative survey from Sri Lanka to test this model and to examine whether and how owner characteristics matter for innovation. The survey also allows analysis of the incidence of innovation in micro and small firms, which have traditionally been overlooked in the study of innovation, despite these firms comprising the majority of firms in developing countries. More than one quarter of microenterprises are found to be engaging in innovation, with marketing innovations the most common. As predicted by our model, firm size is found to have a stronger positive effect, and competition a stronger negative effect, on process and organizational innovations than on product innovations. Owner ability, personality traits, and ethnicity are found to have a significant and substantial impact on the likelihood of a firm innovating, confirming the importance of the entrepreneur in the innovation process.
urn:nbn:de:101:1-20090209329
Keywords: O31; O33; L26; 330; Innovation; microenterprises; SMEs; development; Innovation; Klein- und Mittelunternehmen; Unternehmer; Unternehmensentwicklung; Produktivität; Entwicklung; Sri Lanka